2013
DOI: 10.1021/ol400765a
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Nucleophilic Substitution Reactions of Activated Alkyl Fluorides through Hydrogen Bonding

Abstract: It was discovered that the presence of water as a cosolvent enables the reaction of activated alkyl fluorides for bimolecular nucleophilic substitution reactions. DFT calculations show that activation proceeds through stabilization of the transition structure by a stronger F···H2O interaction and diminishing C-F bond elongation, and not simple transition state electrostatic stabilization. Overall, the findings put forward a distinct strategy for C-F bond activation through H-bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 31 publications
(17 reference statements)
2
44
0
2
Order By: Relevance
“…We have recently published our findings that hydrogen-bond donation from water can activate C-F bonds allowing nucleophilic substitution of activated alkyl fluorides under neutral conditions [10]. During that study, DFT calculations suggested that three water molecules were involved at the transition state of the reaction (Scheme 1A).…”
Section: Introductionmentioning
confidence: 97%
“…We have recently published our findings that hydrogen-bond donation from water can activate C-F bonds allowing nucleophilic substitution of activated alkyl fluorides under neutral conditions [10]. During that study, DFT calculations suggested that three water molecules were involved at the transition state of the reaction (Scheme 1A).…”
Section: Introductionmentioning
confidence: 97%
“…[11,12] Several other applications of C(sp 3 )-F bond activation have been developed, and significant highlights in this vast field of research have recently been reviewed in detail by Hamel and Paquin. Paquin and co-workers have developed methods for chemoselective benzylic-, [13][14][15][16][17] allylic- [13] and propargylic [18] C-F bond activation mediated through hydrogen bonding, reporting that the hydrogen fluoride developed during the reaction would function as an active catalyst, resulting in an autocatalytic kinetic profile. Paquin and co-workers have developed methods for chemoselective benzylic-, [13][14][15][16][17] allylic- [13] and propargylic [18] C-F bond activation mediated through hydrogen bonding, reporting that the hydrogen fluoride developed during the reaction would function as an active catalyst, resulting in an autocatalytic kinetic profile.…”
mentioning
confidence: 99%
“…In water or alcoholic solvent without added triol, low to moderate conversions were observed (12–26%). This was expected since these are all hydrogen bond-donor solvents [17,26]. A low but quantifiable increase in conversion is observed when 2 is added to these reactions, with the best result (35%) being obtained in water (Table 1, entries 1–3).…”
Section: Resultsmentioning
confidence: 83%
“…In summary, we have described that according to our previous proposed mechanism for the hydrogen bond-promoted C–F bond activation [17], simultaneous coordination of the three lone pairs of fluorine by a triol (e.g. 2 ) permits the nucleophilic substitution of benzylic fluorides by amines under neutral and solvent-free conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation